2012
DOI: 10.1371/journal.pone.0034197
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Toxicity of Nanoparticulate CuO and ZnO to Soil Bacterial Communities

Abstract: The increasing industrial application of metal oxide Engineered Nano-Particles (ENPs) is likely to increase their environmental release to soils. While the potential of metal oxide ENPs as environmental toxicants has been shown, lack of suitable control treatments have compromised the power of many previous assessments. We evaluated the ecotoxicity of ENP (nano) forms of Zn and Cu oxides in two different soils by measuring their ability to inhibit bacterial growth. We could show a direct acute toxicity of nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(78 citation statements)
references
References 49 publications
2
75
0
1
Order By: Relevance
“…Rousk et al (2012) found an acute toxic response to soil bacteria from nCuO that did not occur upon exposure to bulk CuO. The growth inhibition EC 50 was found to be around 2254 mg/kg for soil bacteria (Rousk et al, 2012). The principal mechanism of toxicity was found to be dissolution of the metal oxide.…”
Section: Terrestrial Toxicity Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Rousk et al (2012) found an acute toxic response to soil bacteria from nCuO that did not occur upon exposure to bulk CuO. The growth inhibition EC 50 was found to be around 2254 mg/kg for soil bacteria (Rousk et al, 2012). The principal mechanism of toxicity was found to be dissolution of the metal oxide.…”
Section: Terrestrial Toxicity Studiesmentioning
confidence: 97%
“…Generally, growth inhibition does not occur until relatively high exposure concentrations, indicating that other toxic endpoints would not occur at likely environmental concentrations for either nCu or nCuO. Rousk et al (2012) found an acute toxic response to soil bacteria from nCuO that did not occur upon exposure to bulk CuO. The growth inhibition EC 50 was found to be around 2254 mg/kg for soil bacteria (Rousk et al, 2012).…”
Section: Terrestrial Toxicity Studiesmentioning
confidence: 97%
“…The only exception was the nano1-amended BEN soil, in which the pH was significantly higher on days 4 and d 7 ( Figure 3). Interestingly, an increase in soil pH was also observed following 7 h incubation with nano CuO, 24 or 28 d incubation with ZnO. 6 In contrast, the pH of the salt1 soils was initially up to one pH unit lower (i.e., 10-fold higher H + activity) than those of the nano1 soils.…”
Section: Environmental Science and Technologymentioning
confidence: 98%
“…The dissolution of CuO in soils will likely be dominated by proton-consuming hydrolysis at the particle surface (Scheme 1a), 17 a hypothesis supported by the observed increase in soil pH following amendment with CuO nanoparticles. 6,24 Previous research with natural sesquioxides, 25 and recent research on ZnO nanoparticles in soils, 26 has suggested that proton complexation at the oxide surface may be a further mechanism contributing to an increase in pH if the metal oxide point of zero charge is higher than the soil pH. In contrast, the soil pH decreases and dissolved cation concentrations increases on addition of an undersaturated but concentrated solution of Cu salts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…That was evident also from the results of our recent review involving a wide range of aquatic organisms and mammalian cells in vitro showing that the median toxicity of ZnO was stunningly similar to that of the Zn-ions, whatever the organism (Bondarenko et al, 2013a). The fact that low concentrations (below 1 mg/L) of ZnO NPs almost totally dissolve in aqueous media in the order of hours has been proven (for the review, see Ivask et al, 2012) using several analytical methods for quantification of metal-ions: atomic absorption spectroscopy (AAS; Li et al, 2011), graphite furnace atomic absorption spectrometry (GFAAS; Peng et al, 2011), and inductively coupled plasma atomic emission spectroscopy (ICP-AES; Fairbairn et al, 2011;Franklin et al, 2007;Rousk et al, 2012). Indeed, the toxicity of ZnO NPs and Zn salt has been shown to be comparable in the case of algae Pseudokirchneriella subcapitata (Aruoja et al, 2009;Franklin et al, 2007), Thalassiosira pseudonana and Chaetoceros gracilis (Peng et al, 2011) (Cho et al, 2012;Xia et al, 2008;Zhang et al, 2012).…”
Section: Toxicity Of Ag Zno and Cuo Nanoparticles Due To Dissolutionmentioning
confidence: 99%